Субсфера "універсум" як концептуальне поле політичної метафори на матеріалі української та англійської мов - Кабанцева, Надія Вікторівна; Кабанцева, Н. В.; Kabantseva, N. V.; Kabantseva, Nadiia (Дрогобич, 2018)
Cтаттю присвячено дослідженню субсфери «Універсум» («Universum») як концептуального поля складової частини понятійної сфери «Навколишній світ» («Outworld») концептосфери «Політика» на базі української та англійської мов. Вивчено ступінь дослідження та лексико-семантичний рівень субсфери «Універсум». Проаналізована частотність використання метафори в політичному дискурсі представленої субсфери, співвіднесені позитивні, негативні та нейтральні конотації субсфери Універсум» та проведено порівняльний аналіз отриманих статистичних даних на матеріалі української та англійської мов.

The article is devoted to the study of the subsphere «Universum» as a conceptual field of the conceptual sphere «Outworld» in the conceptual sphere «Politics»« on the basis of the Ukrainian and English languages. The person models a political reality, conducting an analogy with the world of living and inanimate nature. The sphere of concepts in the political metaphor on the bases of journalistic discourse of Ukrainian and English languages is filled with cultural and universal specifics. The conceptual sphere «Universum» in the Ukrainian and English languages includes the fundamental outgoing conceptual sphere «Outworld». The phenomena of the external world are included into this sphere, they exist beyond the will of the person, on which he can influence indirectly. Thus, the subsphere «Universum» consists of two concepts: «Space and movement» and «Perception of space». The semantic filling of the concept «Space and movement» is divided into two frames: «Types of space» and «Moving in space». The semantic filling of the concept «Perception of space» is divided into three frames: «Color», «Sound» and «Scent». Consequently, the objective spatial reality of the subsphere «Universum», which includes metaphors for the designation of objects and characteristics of space and movement, movement in space, perception of color, sound, and smell, is likened to objects and subjects of political processes. To the peculiarities of the subsphere «Universum» as a conceptual field of a political metaphor is its heterogeneity, because it includes and describes the phenomena of political life in images that cover the parameters of the world, are universal and can characterize both human activity, the state and space characteristics, color options, processes of moving in space, and so on. To the peculiarities of the subsphere «Universum» as a conceptual field of a political metaphor belongs its heterogeneity, since it includes and describes the phenomena of political life in images that encompass the parameters of the surrounding world. According to the article, the investigation’s degree of research and the lexical-semantic level of the subsphere «Universum» are discovered. The frequency of using the metaphor in the political discourse of the presented subsphere, connotations’ correlation of the subsphere «Universum» is analyzed and the comparative analysis of the obtained statistical data on the material of the Ukrainian and English languages is conducted.
Кабанцева Н. Субсфера "універсум" як концептуальне поле політичної метафори на матеріалі української та англійської мов / Н. Кабанцева // Актуальні питання гуманітарних наук. - 2018. - Вип. 21(1). - С. 78-84. DOI https://doi.org/10.24919/2308-4863.1/21.167161
Keywords: Research Subject Categories::HUMANITIES and RELIGION; концептуальне поле; політика; політична метафора; концептосфера; субсфера; універсум; conceptual field; politics; political metaphor; conceptosphere; subsphere; universum